1994
DOI: 10.1111/j.1365-2885.1994.tb00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral erythromycin formulations in the horse using pharmacokinetic profiles

Abstract: Ewing, P. J., Burrows, G., MacAllister, C, Clarke, C. Comparison of oral erythromycin formulations in the horse using pharmacokinetic profiles. J. vet. Pharmacol, Therap.17, 17–23. The pharmacokinetic properties of four erythromycin formulations were compared in six adult horses after administration of single and multiple oral doses. Formulations of erythromycin administered were estolate and phosphate given 37.5 mg/kg every 12 h and 25 mg/kg every 8 h, and stearate and ethylsuccinate given 25 mg/kg every 8 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 25 publications
2
25
1
Order By: Relevance
“…In contrast to the present results, pharmacokinetic studies on erythromycin including the ethylsuccinate formulation have been reported, showing that much higher dosages (12.5 mgkg bwt, and 25 m a g bwt) given orally in single and multiple doses, respkctively, to mature horses did not cause gastrointestinal disturbances or colitis (Prescott et al 1983;Ewing et al 1994). The results may be indicative of differences in the colon microflora, in particular the presence or absence of potential pathogens and their antibiotic resistance patterns.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the present results, pharmacokinetic studies on erythromycin including the ethylsuccinate formulation have been reported, showing that much higher dosages (12.5 mgkg bwt, and 25 m a g bwt) given orally in single and multiple doses, respkctively, to mature horses did not cause gastrointestinal disturbances or colitis (Prescott et al 1983;Ewing et al 1994). The results may be indicative of differences in the colon microflora, in particular the presence or absence of potential pathogens and their antibiotic resistance patterns.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, erythromycin serum concentrations were more persistent after estolate administration than those after ethylsuccinate form ( t ½λ : 2.92 and 1.53 h, respectively). Similar results have been found in horses (Ewing et al. , 1994) and human beings (Patamasucon et al.…”
Section: Discussionsupporting
confidence: 89%
“…, 1988). In horses, Ewing et al. (1994) studied different erythromycin formulations and found that estolate and ethylsuccinate esters were not absorbed in half of the assayed animals.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is considered as a heat shock protein [18,30,31]. In agreement, HO-1 mRNA expression is induced by hyperthermia in isolated rat hearts [32] and by heat shocks in cultured neonatal cardiomyocytes (Fig. 5).…”
Section: Control Vegf Ho-1mentioning
confidence: 55%